2022
DOI: 10.1007/s10690-022-09393-5
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Volatility Connectedness of Major Environmental, Social, and Governance (ESG) Stock Indices: Evidence Based on DCC-GARCH Model

Abstract: This study investigates the dynamic volatility connectivity of important environmental, social, and governance (ESG) stock indexes from May 2010 to March 2021. The empirical research is focused on five major S&P ESG stock indexes from the US, Latin America, Europe, the Middle East and Africa, and Asia Pacific regions. The study reveals that ESG stock indexes in the Middle East Africa, and Latin America are net shock transmitters, whereas the United States and Asia Pacific are net volatility receivers. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The COVID-19 pandemic has had a profound impact on the global economy, affecting various asset classes in different ways [35]. The connection between green initiatives and ESG scores and how they affected market performance during this crisis is one topic of research.…”
Section: Green Initiatives and Esg Scores On Firm Market Performance ...mentioning
confidence: 99%
“…The COVID-19 pandemic has had a profound impact on the global economy, affecting various asset classes in different ways [35]. The connection between green initiatives and ESG scores and how they affected market performance during this crisis is one topic of research.…”
Section: Green Initiatives and Esg Scores On Firm Market Performance ...mentioning
confidence: 99%
“…For example, Akhtaruzzaman, Boubaker, and Umar (2022) investigated the relationship between the media coverage index (MCI) and ESG leader indices using the TVP-VAR framework of the DY technique and discovered a strong association during the peak of the COVID-19 pandemic when the US was a net receiver of shocks, confirming that the US was the most affected region during the pandemic. According to Shaik and Rehman (2022), ESG stock indices in the Middle East, Africa and Latin America are net shock transmitters, but those in the United States and Asia-Pacific are net volatility receivers. Furthermore, Gao, Li, Zhao, and Wang (2022) use the DY technique to discover that, in most situations, the developed North American market is at the heart of outward risk spillover in global ESG stock markets.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…While, Bouri et al (2021) investigated spillover and connectedness among the oil market, stock market, and foreign exchange market and found spillover among these assets markets. Recent studies have also found a connection between environment, social, and governance stocks (Shaik & Rehman, 2023); financial markets and systematic risk (So et al, 2021); financial market connectedness in G-7 (Das, Rout, & Khatun, 2023); stock market connectedness in BRICS (Hung, 2021a). The outbreak of Covid-19 has caused a significant impact on financial markets worldwide (Baek et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%